2021
DOI: 10.1177/0883073821989164
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Features Associated With SARS-CoV-2 Infection in Children: A Case Series Report

Abstract: Introduction: Although multiple neurologic manifestations associated with SARS-CoV-2 infection have been described in adults, there is little information about those presented in children. Here, we described neurologic manifestations associated with COVID-19 in the pediatric population. Methods: Retrospective case series report. We included patients younger than 18 years, admitted with confirmed SARS-CoV-2 infection and neurologic manifestations at our hospital in Santiago, Chile. Demographics, clinical presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 47 publications
3
55
0
8
Order By: Relevance
“…Additionally, the level of hyperferritinemia identified in our populations and in other MIS‐C studies has been at a much lower degree than what would be required to meet criteria for the HScore, which, along with lack of organomegaly, makes it difficult to meet the HScore criteria ( 15 ). Alternatively, the 2019 MS score likely overestimated CSS in our population, as CNS involvement is one of the largest components of the score and is defined as anything from a headache to seizure, so a vast majority of patients met these criteria ( 16 ). This likely overestimation is seen in the fact that a large proportion of even mild MIS‐C cases were identified as at risk for CSS by the MS score, showing that it does not do well at distinguishing disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the level of hyperferritinemia identified in our populations and in other MIS‐C studies has been at a much lower degree than what would be required to meet criteria for the HScore, which, along with lack of organomegaly, makes it difficult to meet the HScore criteria ( 15 ). Alternatively, the 2019 MS score likely overestimated CSS in our population, as CNS involvement is one of the largest components of the score and is defined as anything from a headache to seizure, so a vast majority of patients met these criteria ( 16 ). This likely overestimation is seen in the fact that a large proportion of even mild MIS‐C cases were identified as at risk for CSS by the MS score, showing that it does not do well at distinguishing disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…In the broader published pediatric literature, neurological manifestations such as smell/taste disorders, headache, seizures, and stroke appear to predominate in acute COVID-19, whereas headache, encephalopathy, and MRI changes suggesting neuroinflammation predominate in MIS-C. Examples of neurological manifestations in children reported to date are summarized by clinical phenotype in Table 1 [ 60 , 61 , 62 ▪▪ , 63 ▪ , 64 , 65 ▪ , 66 , 67 ▪ , 68 75 , 76 ▪ , 77 , 78 ▪ , 79 , 80 ▪▪ ]. As these studies represent different pediatric cohorts (e.g.…”
Section: Neurological Manifestations Of Severe Acute Respiratory Syndrome Coronavirus-2mentioning
confidence: 99%
“…One study conducted in Chile showed 77.7% of patients who had significant improvement in neurologic manifestations of COVID-19/ MIS-C, with persistent dysguesia noted in 2/13 patients and another case series showed 55% of MIS-C patients clinically normal at the time of discharge with minimal residual symptoms. 8 , 12 In contrast, another multicenter study showed that while most patients had transient neurologic symptoms that resolved by the time of discharge, 12% of patients had severe neurologic morbidity with majority of these patients having death or neurologic disability at the time of discharge, 9 which highlights the wide range of outcomes following COVID-19 infection. Several case series and a recent multicenter study have demonstrated the heterogeneity of neurologic clinical and radiographic manifestations of MIS-C, and our case is an additional example of that.…”
Section: Discussionmentioning
confidence: 99%